Day‐to‐day variability of insulin requirements in the inpatient setting: Observations during fully closed‐loop insulin delivery. Issue 8 (4th May 2021) - Boughton, Charlotte K.; Daly, Aideen; Thabit, Hood; Hartnell, Sara; Herzig, David; Vogt, Andreas; Ruan, Yue; Wilinska, Malgorzata E.; Evans, Mark L.; Coll, Anthony P.; Bally, Lia; Hovorka, Roman
Abstract: The aim of this study was to characterize the variability of exogenous insulin requirements during fully closed‐loop insulin delivery in hospitalized patients with type 2 diabetes or new‐onset hyperglycaemia, and to determine patient‐related characteristics associated with higher variability of insulin requirements. We retrospectively analysed data from two fully closed‐loop inpatient studies involving adults with type 2 diabetes or new‐onset hyperglycaemia requiring insulin therapy. The coefficient of variation quantified day‐to‐day variability of exogenous insulin requirements during up to 15 days using fully automated closed‐loop insulin delivery. Data from 535 days in 67 participants were analysed. The coefficient of variation of day‐to‐day exogenous insulin requirements was 30% ± 16%, and was higher between nights than between any daytime period (56% ± 29% overnight [11:00 pm to 4:59 am ] compared with 41% ± 21% in the morning [5:00 am to 10:59 am ], 39% ± 15% in the afternoon [11:00 am to 4:59 pm ] and 45% ± 19% during the evening [5:00 pm to 10:59 pm ]; all P  < 0.01). There is high day‐to‐day variability of exogenous insulin requirements in inpatients, particularly overnight, and diabetes management approaches should account for this variability.